The primary productivity of phytoplankton and related ecological parameters in Vung Ro bay (Phu Yen) - Huan, Nguyen Huu; Duc Hieu, Nguyen Trinh (Academia Journal of Biology, 2016)
The primary productivitiy of phytoplankton and relative ecological parameters in Vung Ro bay (Phu Yen) are described and discussed from collected and observed data during 2014-2015. Overall, the primary productivity of phytoplankton in Vung Ro bay is relatively high. The primary productivity in the northeast waters of the bay where the aquaculture has being developed (fish and shrimp cages) is the highest. The primary productivity of phytoplankton in Vung Ro bay is higher than that in some coastal waters of the South of Vietnam central part (Nha Phu lagoon, Nha Trang bay, etc.) and Me Kong delta, but lower than Binh Dinh coastal waters. The variation of observed ecological factors of the Vung Ro bay in the dry season is stronger than that in the rainy season, but within the limits of the Vietnammese regulation for coastal water quality. Citation: Nguyen Huu Huan, Nguyen Trinh Duc Hieu, 2017. The primary productivity of phytoplankton and related ecological parameters in Vung Ro bay (Phu Yen). Tap chi Sinh hoc, 39(1): 40-50. DOI: 10.15625/0866-7160/v39n1.7885. *Corresponding author: nghhuan@gmail.com. Received 14 March 2016, accepted 20 March 2017